Modelling of arch dam foundation failure scenarios - case studies of Baixo Sabor and Alto Ceira dams - Lemos, J. V. (2011)
In concrete arch dam foundations, potential failure mechanisms are typically defined by natural rock discontinuities or the concrete-rock interface. Discrete element models are particularly adequate for the safety assessment of these failure scenarios, given their ability to represent the geologic structure of the rock mass, as well as the concrete cantilevers. Application of these procedures to 2 large dams presently under construction in Portugal, Baixo Sabor and Alto Ceira arch dams, is presented. The numerical models represent the foundation rock mass as a system of deformable blocks defined by the main faults and joint sets identified at the site. The safety analysis is performed by progressive reduction of strength along the discontinuities until the failure condition is reached.